SCIENTOMETRIC ANALYSIS OF DIGITAL BANKING: FUTURE ISLAMIC DIGITAL BANK IN INDONESIA - Riani, Ririn; Rusydiana, Aam Slamet (IJIBE (International Journal of Islamic Business Ethics), 2022)
This study maps out research related to the development of research trends in digital banking themed papers published by leading journals that have been indexed by Scopus from 1976 to 2021. The analysis focuses on trends in keywords, authors and journals of 873 digital banking themed papers. publication. The results of the scientometric analysis mapping are then studied more deeply to review development strategies related to digital banking that can be adopted by Islamic banking in Indonesia. This study uses descriptive statistical methods and bibliometric analysis using biblioshiny R software to determine bibliometric maps. The flow of economic digitization requires banks to transform in order to maintain their role and position as the main intermediary institution in the financial system as well as the transmission axis of monetary policy. Digital transformation requires banks to be able to adapt the business innovation model used, organizational structure, work culture, and infrastructure they have. Islamic banking is required to be a solution by offering services and innovations through digital channels. The main thing is how to find the right balance between efforts toÂ optimize opportunities and carry out various digital innovations in an effort to increase market share in the future.Â